Development in Islamic Debt Securities: Establishing Malaysia as an International Islamic Capital Market Centre - Harun, Mukaramah; Che Mat, Siti Hadijah; Sabudin, Noor Sa'adah (Universiti Putra Malaysia, 2007)
The Islamic capital market is a niche market in which Malaysia has a comparative and competitive advantage and represents a potentially significant area where Malaysia can effectively position itself at the global forefront. Malaysia has seen significant development and expansion in the Islamic equity and bond markets over recent years. The nation has also earned a reputation as one of the pioneers in Islamic capital market-related research and development.